In vitro acute toxicity of metal-based nanoparticles in human trophoblast BeWo b30 cells - Pires, J. (2022)
Abstract publicado em: Toxicol Lett. 2021 Sep;350 (Suppl):S110. doi: 10.1016/S0378-4274(21)00229-0